Kontribusi Ekonomi Perempuan Penjual Ayam Goreng Gerobak di Beberapa Pasar Satelit di Kota Padang - Dwi Yuzaria; Fitrini Fitrini (Jurnal Agripet, 2011)
Economical contribution of women in merchant-chart-fried chicken business in satellite market in padang cityABSTRACT. As social-economic demands increased, the complexity of family needs grew higher. To fulfill them, woman has to take part in making a living. This research aims to see economical performance of women in running merchant-cart-fried-chicken, identifying the obstacles faced and giving alternatives of solution. This research was conducted by survey method, with respondents of merchant-cart-fried-chicken seller in several markets in Padang city. Sample was taken with proportional allocation of 15 people. Data was analyzed by descriptive analysis method. The research showed that economical performance of women merchant-cart-fried-chicken seller is low with working hour o5 5.07 hours/day. Percentage of women that take part in all activities start from planning to marketing is 32.5%. This is a potential business to develop, with average income 92.259,58 IDR/day and average R/C ratio 1.29. Internal constraints were family relation pattern that scoped womens part in fulfilling family need, meanwhile the external constraints were the difficulties in acquiring more capital to develop the business and the price fluctuation of chicken as a main raw material. Alternative solution that can be offered was opening the business at home so that women can spare more time to work the business and accessing soft loan with light requirements. The conclusion of the research was that women took part in making a living for the family, however the contribution is low due to patriarchy value as an internal constraint and capital problem as external constraint. The solution offered was taking soft loan and building relation with raw material supplier.